HARMONISASI HUKUM PENGATURAN DESA OLEH KEMENTERIAN DALAM NEGERI DAN KEMENTERIAN DESA, PEMBANGUNAN DAERAH TERTINGGAL, DAN TRANSMIGRASI PASCA BERLAKUNYA UNDANG UNDANG NO. 6 TAHUN 2014 TENTANG DESA - Rooza Meilia Anggraini (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
After the Presidential Decree No. 165 year of 2014 on the Tasks Arrangement and Functions of the Working Cabinet was issued, there is a trade-off in the authority of the rural areas management between the Ministry of Domestic Affairs and the Ministry of Village, Underdeveloped Regions, and Transmigration. There was disharmony between the the Minister of Domestic Affairs and of Village, Underdeveloped Regions and Transmigration in terms of the governance arrangement of the authority of the village government and of any financial collection and the arrangement of the village fund. There have been four Legal efforts made to harmonize the two ministries: horizontal harmony, joint decision letters, repeal or cancelation by the related institutions or the institutions above them and executive or judicative reviews. Executive review is the testing rights adherent to the executive institution to test any legislation and to cancel it if it seems to be in contradiction with the higher legislation of with public interest. Judicative review is the testing of a legislation under the law by the Supreme Court. Keyword : Harmonization, Ministry of Domestic Affairs, Ministry of Village, Underdeveloped Regions, and Transmigration